Mixing MTA with phosphate buffered solution can improve its physical properties and increase favorable outcome - Naghmeh Meraji (Wolters Kluwer Medknow Publications, 2014)
Introduction: Encountering environmental situations that have an adverse effect on the properties of Mineral Trioxide Aggregate (MTA) is inevitable and unfortunately common. In many cases MTA does not set and the clinician is forced to apply this cement again. This occurrence may affect the outcome of endodontic treatments such as perforation repair. Therefore, strategies should be considered to overcome this matter. Various studies have been conducted that mixed several substances with MTA to reverse the adverse effects on this material but still we face this problem. The Hypothesis: In this paper, we propose a hypothesis that mixing MTA with phosphate buffered solution (PBS) may reverse the adverse environmental effects and may help us overcome this clinical problem. Evaluation of the Hypothesis: PBS is a synthetic solution containing phosphate which is commonly used for mimicking in vivo situations in laboratory studies. Considering that some studies have shown that when MTA encounters tissue fluids containing phosphorous its properties improve, we suggest that mixing this cement with PBS can at least reverse the adverse effect of the environment. It should be noted that the better the properties of these cements, the better the outcome of treatment can be.